CLASSIFICATION OF LANDSCAPE VOCABULARY IN UZBEK AND ENGLISH - O’rozboyeva Mavluda Shukurlo qizi (Ta'lim innovatsiyasi va integratsiyasi, 2026)
This article explores the classification of landscape vocabulary in Uzbek and English. It examines how natural features such as mountains, plains, rivers, forests, deserts, and coastal regions are expressed in both languages. The study highlights the semantic similarities and differences between Uzbek and English landscape terms, and emphasizes  their  role  in  describing  geography,  ecology,  and  the  environment. Understanding  these  words  helps  learners  improve  their  descriptive  abilities  and communicate more effectively about the natural world in both languages.